Crash course : from the good war to the forever war - Franklin, H. Bruce (Howard Bruce), 1934-2024 (Rutgers University Press, 2018)
Growing up during the Second World War, H. Bruce Franklin believed what he was told: that America's victory would lead to a new era of world peace. Like most Americans, he was soon led to believe in a world-wide Communist conspiracy that menaced the United States, forcing the nation into a disastrous war in Korea. But once he joined the U.S. Air Force and began flying top-secret missions as a navigator and intelligence officer, what he learned was eye-opening. He saw that even as the U.S. preached about peace and freedom, it was engaging in an endless cycle of warfare, bringing devastation and oppression to fledgling democracies across the globe. Now, after fifty years as a renowned cultural historian, Franklin offers a set of hard-learned lessons about modern American history. Crash Course is essential reading for anyone who wonders how America ended up where it is today: with a deeply divided and disillusioned populace, led by a dysfunctional government, and mired in unwinnable wars. It also finds startling parallels between America's foreign military exploits and the equally brutal tactics used on the home front to crush organized labor, antiwar, and civil rights movements. More than just a memoir or a history book, Crash Course gives readers a unique firsthand look at the building of the American empire and the damage it has wrought. Shocking and gripping as any thriller, it exposes the endless deception of the American public, and reveals from inside how and why many millions of Americans have been struggling for decades against our own government in a fight for peace and justice.
Keywords: Historians -- United States -- Biography.; Vietnam War, 1961-1975 -- Protest movements.; War and society -- United States -- History -- 20th century.; United States -- History, Military -- 20th century.; États-Unis -- Histoire militaire -- 20e siècle.; Historiens -- États-Unis -- Biographies.; Guerre du Viêt-nam, 1961-1975 -- Contestation.; Guerre et société -- États-Unis -- Histoire -- 20e siècle.; HISTORY -- General.; Historians; Protest movements; War and society; United States; 1900-1999; Military history; Biographies; History